Скифский курган у с. Калиновка в Надпорожье - Ромашко, А.В.; Крылова, Л.П. (Археологія і давня історія України, 2019)
Статья посвящена анализу погребального обряда скифского погребения у с. Калиновка, в инвентаре которого присутствует часть стенки металлического котла. Проведено хронологическое определение комплекса, установлен возможный статус погребенного в социальной структуре скифского социума. In 1973 Dnipropetrovsk Yavornitsky National Historical Museum conducted archaeological rescue works near the village Kalinovka, Solonyansky district, Dnipropetrovsk region. Scythian barrow 2 was the 4 m high with a diameter up to 30 m. The mound was surrounded with the circle of the stone blocks. Four Scythian burials were discovered. Three of them belong to children of different ages, one — to the family. All burials were in destroyed catacomb graves. The skeletons lied supine with their head directed to the east. They were accompanied by gold and bronze jewelry and glass beads.